1980
DOI: 10.1007/bf02906182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibitors on synthesis of fatty acyl chains present in waxes on developing maize leaves

Abstract: Free fatty acids were identified as the fifth lipid class in wax from green leaf segments. They were not isolatable from the wax on yellow leaf segments, which also lacked aldehydes and appeared to have more esters and alkanes than primary alcohols. The chain length spectra of the alkanes and both ester moieties from yellow tissue are distinguishable from those of green tissue by the prominent amounts of shorter homologues, but the homologue distributions of the aldehydes and primary alcohols from the two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Presently available evidence suggests that de novo fas synthesis in plant epidermal cells gives rise to the substrates for the wax elongase which is located in the plasmalemma and/or cell walls of the same cells (see 1 1). Differential modification of the biosynthesis of the wax carbon chains by inhibitors, genetic mutation and photoperiodic treatments are best interpreted by the existence of several elongases (see 18,2,19). Before arriving on the cuticle surface, the resulting pools of fatty acyl chains can either serve as substrates for associated pathways such as decarboxylation or reduction, or simply be relased from the elongase(s) as free acids (see 18).…”
Section: Discussionmentioning
confidence: 99%
“…Presently available evidence suggests that de novo fas synthesis in plant epidermal cells gives rise to the substrates for the wax elongase which is located in the plasmalemma and/or cell walls of the same cells (see 1 1). Differential modification of the biosynthesis of the wax carbon chains by inhibitors, genetic mutation and photoperiodic treatments are best interpreted by the existence of several elongases (see 18,2,19). Before arriving on the cuticle surface, the resulting pools of fatty acyl chains can either serve as substrates for associated pathways such as decarboxylation or reduction, or simply be relased from the elongase(s) as free acids (see 18).…”
Section: Discussionmentioning
confidence: 99%
“…When a wax coating is reasonably dense, such as that of barley basal leaf sheaths (Figure 10), barley and most wheat leaf blades (e.g., 22,29) and other surfaces high in primary alcohols (e.g., 3,6,12,14,22,29), it is often difficult to discriminate between individual plates and to characterize their shape. A technique that might be useful in this respect is that of negative staining which has been successfully used in studies of wax tubes (3,15,16). The plates were gently removed by a drop of staining solution when it was touched to the cuticle surface (31).…”
Section: Structure Of Plate Waxesmentioning
confidence: 99%
“…Differences observed in the n-alkane composition with respect to fruit position on the tree suggests a possible effect of light and of temperature on the physiology or biochemistry of wax formation and deposition. This suggestion is presented because the SW quadrant receives higher amounts of direct sunlight and is typically warmer than the NE quadrant, and that light (Macey, 1970;Giese, 1975;Avato et al, 1980) and temperature (Giese, 1975) are reported to influence synthesis of wax components. Such environmental factors have been shown to influence other fruit characteristics.…”
Section: Resultsmentioning
confidence: 99%